Local space and free space: the interaction between Southern scholars and the literary public sphere of Hong Kong - Lim, Choon Bee; Ser, Wue Hiong; Wang, Weizhou (Universidad de Salamanca * Ediciones, 2025)
This work focuses on how Southern literati changed the formation and development of Hong Kong’s literary public sphere during wartime. These intellectuals run away from political instability in mainland China, which is filled with coupled high-brow culture hence enriching the cultural potential of Hong Kong. The paper concerns cultural preservation and artistic freedom and shows two of the leading cultural personas, Hu Shi and Sa Kong. By analyzing the newspapers, periodicals and the literary works of Xiao Hong, the research aim to emphasize the important role of the media as a tool for cultural interchange. Through engagements with Xiao Hong’s literary works produced in Hong Kong, one can examine how the city served as a free space that fostered arts and culture. It seems to highlight the need for the reconciliation of the old and the new as well as the Southern literati’s tradition in defining the literary Hong Kong. Future developments include examining relatively unknown scholars, and analysis of various cities during war and exile.